A Valid and Reliable Tool to Assess Nursing Students` Clinical Performance - Pazargadi, Mehrnoosh; Ashktorab, Tahereh; Khosravi, Sharareh; Alavi majd, Hamid (International Journal of Advanced Nursing Studies, 2013)
Background: The necessity of a valid and reliable assessment tool is one of the most repeated issues in nursing students` clinical evaluation. But it is believed that present tools are not mostly valid and can not assess students` performance properly.Objectives: This study was conducted to design a valid and reliable assessment tool for evaluating nursing students` performance in clinical education.Methods: In this methodological study considering nursing students` performance definition; the tool, its domains and items were specified through expert interviews and literature review. To determine validity; face validity (using expert viewpoints and item impact method) and content validity (using expert viewpoints, content validity ratio and content validity index) were considered. Reliability was evaluated through Cronbach`s alpha and interclass correlation (ICC).Results: Seven domains and 55 items were found and the primary tool was designed. Item impact score and content validity ratio were 1.5 and more and 0.54 and more for each item, respectively and total content validity index was 0.94. Cronbach`s alpha for the whole tool was 0.992 and ICC was 0.89.Conclusion: The designed tool with a high validity and reliability is considered proper and can be used for evaluating nursing students` clinical performance.